(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article analyses that they are all made to have a proverbial effect, in other words, they meet the same objective: to influence, to make the recipient act. Also, as they are considered as genres of the spoken language, the boundaries of their distinction remain fine. Oralism does not feel the need to define, unlike the scriptural which is obliged to classify, to describe. It is important to emphasize that paremiologists do not always agree with the restriction of paremiology to folkloric, sociological or even anthropological aspects, because in their opinion paremies are not limited to these considerations alone and that it is should be approached from a linguistic point of view. In other words, proverbs represent a particular type of discourse that deserves to be studied.